Association of levels of opioid use with pain and activity interference among patients initiating chronic opioid therapy: a longitudinal study. Issue 4 (April 2016) - Turner, Judith A.; Shortreed, Susan M.; Saunders, Kathleen W.; LeResche, Linda; Von Korff, Michael
Abstract : Abstract: Little is known about long-term pain and function outcomes among patients with chronic noncancer pain initiating chronic opioid therapy (COT). In the Middle-Aged/Seniors Chronic Opioid Therapy study of patients identified through electronic pharmacy records as initiating COT for chronic noncancer pain, we examined the relationships between level of opioid use (over the 120 days before outcome assessment) and pain and activity interference outcomes at 4- and 12-month follow-ups. Patients aged 45+ years (N = 1477) completed a baseline interview; 1311 and 1157 of these comprised the 4- and 12-month analysis samples, respectively. Opioid use was classified based on self-report and electronic pharmacy records for the 120 days before the 4- and 12-month outcome assessments. Controlling for patient characteristics that predict sustained COT and pain outcomes, patients who had used opioids minimally or not at all, compared with those with intermittent/lower-dose and regular/higher-dose opioid use, had better pain intensity and activity interference outcomes. Adjusted mean (95% confidence interval) pain intensity (0-10 scale) at 12 months was 4.91 (4.68-5.13) for the minimal/no use group and 5.71 (5.50-5.92) and 5.72 (5.51-5.93) for the intermittent/lower-dose and regular/higher-dose groups, respectively. A similar pattern was observed for pain intensity at 4 months and for activity interference at both time points. Better outcomes in the minimal/no use group could reflect pain improvement leading to opioid discontinuation. The similarity in outcomes of regular/higher-dose and intermittent/lower-dose opioid users suggests that intermittent and/or lower-dose use vs higher-dose use may confer risk reduction without reducing benefits. Abstract : At 1-year follow-up, pain and interference levels of regular/higher-dose and intermittent/lower-dose opioid users were similar, and worse than those of patients with minimal/no opioid use.